Effects of a Two-Year Home-Based Exercise Training Program on Oxidized LDL and HDL Lipids in Coronary Artery Disease Patients with and without Type-2 Diabetes - Tiainen S; Kiviniemi A; Hautala A; Huikuri H; Ukkola O; Tokola K; Tulppo M; Vasankari T (MDPI, 2022)
We investigated the effect of two-year home-based exercise training program on oxidized low-density lipoprotein LDL (ox-LDL) and high-density lipoprotein HDL (ox-HDL) lipids in patients with coronary artery disease (CAD), both with and without type-2 diabetes (T2D). Analysis of lipoprotein-oxidized lipids was based on the determination of baseline conjugated dienes in lipoprotein lipids. In order to study the effect of an exercise load on ox-LDL and ox-HDL lipids patients in both CAD and CAD + T2D intervention, groups were divided in three based on exercise load (high, medium, and low). During the two-year home-based exercise training program, the study showed that only higher training volume resulted in a decreased concentration of ox-LDL, while the two groups with lower training volumes showed no change. This result indicates that the training load needs to be sufficiently high in order to decrease the concentration of atherogenic ox-LDL lipids in patients with CAD and CAD + T2D. Interestingly, the concentration of ox-HDL did not change in any of the subgroups. This could indicate that the lipid peroxide-transporting capacity of HDL, suggested by results from exercise training studies in healthy adults, may not function similarly in CAD patients with or without T2D. Moreover, the lipid-lowering medication used may have had an influence on these results.